2022
DOI: 10.1371/journal.pone.0274944
|View full text |Cite
|
Sign up to set email alerts
|

What are the impacts of increasing cost-effectiveness Threshold? a protocol on an empirical study based on economic evaluations conducted in Thailand

Abstract: Background Economic evaluations have been widely used to inform and guide policy-making process in healthcare resources allocation as a part of an evidence package. An intervention is considered cost-effective if an ICER is less than a cost-effectiveness threshold (CET), where a CET represents the acceptable price for a unit of additional health gain which a decision-maker is willing to pay. There has been discussion to increase a CET in many settings such as the United Kingdom and Thailand. To the best of our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The HBIG-free intervention with TDF prophylaxis was the most cost-effective option . +Cost-effectiveness threshold in Thailand is 160 000 THB per QALY, 18 and QALY of chronic HBV infection was 13.6 years. 19 ICER, incremental cost-effectiveness ratio; TDF, tenofovir disoproxil fumarate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HBIG-free intervention with TDF prophylaxis was the most cost-effective option . +Cost-effectiveness threshold in Thailand is 160 000 THB per QALY, 18 and QALY of chronic HBV infection was 13.6 years. 19 ICER, incremental cost-effectiveness ratio; TDF, tenofovir disoproxil fumarate.…”
Section: Discussionmentioning
confidence: 99%
“…The cost per infection averted results were compared against Thailand’s cost-effectiveness threshold that explicitly defined since 2013 that they are willing to pay 160 000 THB per quality-adjusted life year (QALY). 18 QALY gained for chronic HBV infection in Thailand was 13.6 life-years from previous publication, calculated by modelling of direct (medical and non-medical) and indirect costs in Thailand of patients aged 30 years old who would be giving standard chronic hepatitis B treatment that could have 13.6 QALYs gained. 19 We selected the best two cost-effective interventions to test for impact of each of the stated parameters on ICER.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 A recent systematic review found that 17 countries have officially recognised CETs. 7 Among these countries, England (£20 000–30 000 per QALY), 8 Thailand (160 000 Thai baht per QALY), 9 Ireland (€45 000 per QALY) 10 and Norway (500 000 Norwegian krone) 10 have explicit CETs. For most of the countries which lack formal thresholds, indicative CETs gauged by gross domestic product (GDP) per capita are often used alternatives, 11 especially in low-income and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%